Master Plan Initiative of Electronic-Based Government System (SPBE) in Metro City, Indonesia - Erizal Erizal; M Fairuzabadi; Zaidir Zaidir; A Roswiani (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
The central government expects the development of information technology and bureaucratic reform in the regions to be more focused and integrated. The problem that exists in the Metro City government is that there are still many government service information systems that have not been integrated or are still partial. The Metro City government's Electronic-Based Government System Index (SPBE) in 2021 is 2.17 with the predicate "Enough", even though the desired condition in 2026 is "Good" so the SPBE index value must be achieved is at least 2.6. The purpose of this research is to prepare the SPBE Master Plan within the scope of the vision and mission, architecture, policy direction, and roadmap for the next 5 years. The SPBE master plan document was created to provide an overview and direction for the management of Information Systems and Information Technology resources for the Metro City government. The methods used in this research are qualitative and quantitative. Primary data were collected through questionnaire forms, interviews, and Focus Group Discussions. The steps taken are to analyze the Metro City SPBE index as a result of the 2020 evaluation and SWOT analysis which will produce the factors of weakness, opportunities, and threats in the SPBE implementation to further formulate strategies in the SPBE domain. The result of this research is a Metro City government SPBE master plan document for 2022-2026 with policy directions and strategies for developing SPBE governance, developing SPBE services, developing human resources, and developing SPBE information and communication technology.